Profile of Liver Cirrhosis Patients at Imelda Pekerja Indonesia General Hospital (RSU IPI) Period January 2020 – December 2021 - Salomo Lumbantobing; Chairul Radjab Nasution; Fiska Maya Wardhani (HM Publisher, 2023)
Liver cirrhosis is the result or complication of a chronic liver condition where the liver parenchyma is damaged so that its function decreases. This study aims to study the profile of patients with liver cirrhosis at the Imelda Pekerja Indonesia General Hospital in Medan for the period January 2020 - December 2021. This study is a descriptive observational study. A total of 40 samples of medical records of patients with a diagnosis of liver cirrhosis at the Imelda Pekerja Indonesia General Hospital in (IPI) Medan were included in this study. Univariate analysis in the form of frequency distribution data tabulation was used to present the data. The results showed that most patients with liver cirrhosis were male (72.5%), aged 56-65 years (32.5%), and the main complaint was nausea and vomiting (47.5%). The most physical examination results were ascites (52.5%), abnormal lab results were increased SGPT (75%), SGOT (80%), total bilirubin (85%), prothrombin time (75%) and decreased albumin (85%) and Hb (55%), most of the patients were in the category of Child-Pugh Score B (37.5%) and C (37.5%), and the most complication was hepatorenal syndrome (55%). In conclusion, the profiles of patients with liver cirrhosis are mostly male, aged 56-65 years, with the most complaints of nausea and vomiting and the most physical examination findings of ascites. There was an increase in SGPT, SGOT, total bilirubin, and prothrombin time, as well as a decrease in albumin and Hb.